PTSD in French Adolescent Victims Following the London Attack in March 2017: Data From the First Step of the AVAL Study - Coulon, Nathalie; Grenon, Marion; Consigny, Maëlys; Simson, J-P (Frontiers in Psychiatry, 2022)
Background The terrorist attack at Westminster Bridge on March 22nd, 2017 impacted on French high school students on a school trip in London. This terrorist attack was claimed by the Islamic State. The aim of the study was to assess the mental health consequences of the attack on the French adolescents who were directly exposed (criteria A for Post-Traumatic Stress Disorder, PTSD). This involved three dimensions, namely: 1) clinical; 2) epidemiological; and 3) pre-vention and therapeutic. Material and method The investigation was the first observational step of AVAL (Adolescents Victimes de l’Attentat de Londres) study, a cohort monitoring project and it was then a monocentric, cross sectional, non interventional survey, at only one-year post-trauma. The study was carried out utilizing self- and clinician-administered questionnaires. Volunteers from the medico-psychological emergency unit provided support for these victims during the study protocol. Results From the target population (n = 53), 39 adolescents (73.6%) agreed to participate, with a median age 16.9 years. 12 months after the attack, 25.6% of teenagers suffered from current PTSD (p<0.0001). Those with, vs without, PTSD showed several significant differences: 1) heightened levels of major depressive episodes (p=0.0266) and suicidality (p=0.0164); 2) increased substance use, including tobacco (p=0.0284) and cannabis (p=0.0449); and 3) im-paired functioning in school (p=0.0203), social (p<0.0001) and family (p<0.0001) settings. 64.1% of directly exposed teenagers also had a current psychiatric disorder other than PTSD. Discussion The heightened levels of PTSD, psychiatric disorders, and substance use at 12 months high-light the importance of early intervention in adolescents exposed to terrorist-linked potential-ly traumatic events. Clinical Trial Registration: www. ClinicalTrials.gov, identifier NCTO34932433 Ethics: The regional ethics committee (Comité de Protection des Personnes Ouest IV – Nantes) approved the study protocol (Reference 10/18_3). All participants (and their legal guardians, for minors) must sign the informed consent to participate.